2018
DOI: 10.1177/0032885518793952
|View full text |Cite
|
Sign up to set email alerts
|

Of All the Joints, She Walks Into This One: Career Motivations of Women Corrections Executives

Abstract: While the number of female corrections executives is small, there is evidence that those moving up the ranks in this highly male-dominated field continue to grow. The present study, conducted with support from the Association of Women Executives in Corrections (AWEC), found that 18% of state corrections agencies were led by women. While women corrections executives' motivations for entering the field were diverse, they centered primarily on pay and benefits. Notably, most women executives entered the correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Even though women may rise in corrections from varied positions, it remains more difficult to do this from jobs associated with feminine characteristics (i.e., treatment vs. custodial positions). Women who advance from a noncustodial/treatment trajectory have more difficulty moving up in rank, particularly on the operations side and within state corrections systems (Collica-Cox & Schulz, 2018). Such difficulties may result from gender bias where certain positions and their related responsibilities, such as those grounded in treatment and essentially feminized, are not viewed as prestigious or as important as those jobs where the main responsibilities involve the custodial care and maintenance of prisoners, which are essentially masculinized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though women may rise in corrections from varied positions, it remains more difficult to do this from jobs associated with feminine characteristics (i.e., treatment vs. custodial positions). Women who advance from a noncustodial/treatment trajectory have more difficulty moving up in rank, particularly on the operations side and within state corrections systems (Collica-Cox & Schulz, 2018). Such difficulties may result from gender bias where certain positions and their related responsibilities, such as those grounded in treatment and essentially feminized, are not viewed as prestigious or as important as those jobs where the main responsibilities involve the custodial care and maintenance of prisoners, which are essentially masculinized.…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns have been detected in corrections; recent studies have found that the majority of male and female officers feel there are opportunities for advancement and fairness in the promotion process (Collica-Cox & Schulz, 2019b;Lambert et al, 2007). Most women executives in corrections, just as their policing counterparts, highly recommend it as a career to other women (Collica-Cox & Schulz, 2018). As women advance, they are more likely to be recognized as effective and competent leaders since difficulties in advancement, even in typically maledominated jobs, dissipate as women spend more time on their jobs (Rabe-Hemp, 2009).…”
Section: Tokenism and Women In Correctionsmentioning
confidence: 99%
“…The most cited reasons were the job security, opportunities for advancement, early retirement with good pay, and the ability to keep the community safe (Schlosser et al, 2010). The salience of pay and benefits as a primary draw for this line of work has been corroborated by virtually every study examining the motivations for choosing correctional officer positions (Burton, Jonson, Miller, Petrich, & Burton, 2022; Collica-Cox & Schulz, 2018; Lombardo, 1981; Ricciardelli et al, 2022; Ricciardelli & Martin, 2017). Furthermore, Burton, Jonson, Miller, Petrich, and Burton (2022) recently reported several other motivations officers gave for choosing the occupation, which included opportunities to help rehabilitate individuals serving time in prisons and to protect society from harm.…”
Section: Choosing the Correctional Officer Professionmentioning
confidence: 99%
“…While many studies find service (i.e., helping others) to be a common motivation for working in policing, what drives individuals to work in corrections is more likely to include financial motivations (Collica-Cox & Schultz, 2018;Schlosser et al, 2010). A mixed methods study of 83 female correctional executives revealed participants were motivated by being able to make difference, good pay, and excellent benefits, with minimal distinctions between Black and white respondents (Collica-Cox & Schulz, 2018). Similarly, financial incentives are also commonly reported as driving motivators for individuals interested in pursuing legal careers (Carrol & Brayfield, 2007).…”
Section: Motivations To Work In the Criminal Justice Systemmentioning
confidence: 99%
“…Second, this study is the first to incorporate the role of skin tone on motivations to work in the criminal justice system. Racial and ethnic identity can influence the primary motivating factors individuals report for aspiring to work in the criminal justice system (Collica-Cox & Schulz, 2018;Gabbidon et al, 2003;Tartaro & Krimmel, 2003). In other words, individuals of different racial/ethnic identities provide similar rationales for their career choice -but in different orders or to varying degrees.…”
Section: Contributionmentioning
confidence: 99%